2014
DOI: 10.5253/078.102.0105
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrian Density Influences Flight Distances of Urban Birds

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 47 publications
1
29
1
1
Order By: Relevance
“…Many studies of escape behavior in birds focused on the influence of external factors affecting behavioral responses: habitat quality (Burger, Gochfeld, Jenkins, & Lesser, 2010), the direction of approach by predators (Møller & Tryjanowski, 2014), intruder starting distance (Blumstein, 2013;Glover et al, 2011), number or density of intruders (Geist, Liao, Libby, & Blumstein, 2001), population density (Mikula, 2014), urbanization (Samia et al, 2017), road speed limits (Legagneux & Ducatez, 2013), insular distribution (Cooper, Pyron, & Garland, 2014), predator-prey interactions (Møller, 2008b), spatial gradients of predator abundance (Díaz et al, 2013), or daytime and season when FID was measured (Burger & Gochfeld, 1991;Piratelli, Favoretto, & de Almeida Maximiano, 2015). Blumstein (2006) has made links between escape behavior and life history and natural history traits (e.g., diet) in birds.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies of escape behavior in birds focused on the influence of external factors affecting behavioral responses: habitat quality (Burger, Gochfeld, Jenkins, & Lesser, 2010), the direction of approach by predators (Møller & Tryjanowski, 2014), intruder starting distance (Blumstein, 2013;Glover et al, 2011), number or density of intruders (Geist, Liao, Libby, & Blumstein, 2001), population density (Mikula, 2014), urbanization (Samia et al, 2017), road speed limits (Legagneux & Ducatez, 2013), insular distribution (Cooper, Pyron, & Garland, 2014), predator-prey interactions (Møller, 2008b), spatial gradients of predator abundance (Díaz et al, 2013), or daytime and season when FID was measured (Burger & Gochfeld, 1991;Piratelli, Favoretto, & de Almeida Maximiano, 2015). Blumstein (2006) has made links between escape behavior and life history and natural history traits (e.g., diet) in birds.…”
Section: Introductionmentioning
confidence: 99%
“…Frequent non‐threatening exposure to humans in these areas may result in shorter FID compared to hyrax populations in kopjes lacking human presence. Studies on bird FID in relation to varying levels of non‐threatening human disturbance found a decrease in FID with increasing exposure rates (Engelhardt & Weladji, ; Malo, Acebes, & Traba, ; McGowan et al, ; Mikula, ).…”
Section: Introductionmentioning
confidence: 99%
“…The decision as to when to flee from a potential threat weighs the various opportunity and energetic costs of escape against the probability of mortality (Ydenberg and Dill, 1986;Cooper, 2015b). These costs are themselves dependent on numerous intrinsic and extrinsic factors including habitat type and openness (Martin and López, 1995); temperature (in ectotherms) (Hertz et al, 1982); sex (Lailvaux et al, 2003); and the presence of humans (Mikula, 2014). That urban populations of birds allow closer approach of humans before initiating escape compared to rural ones has been attributed to habituation to human presence (Cooke, 1980;Blumstein, 2014).…”
Section: Escape Behaviormentioning
confidence: 99%